From App to Accent: How Duolingo Shapes Student Speaking Skills - Robiatul Ainun; Usuluddin; Muhammad Adib Nazri; Ary Prasetyaningrum (Explorations in English Learning, 2025)
Language learning in secondary education increasingly integrates technology to address persistent challenges in students’ English proficiency, particularly vocabulary mastery. Vocabulary plays a crucial role in supporting all language skills, and limited lexical knowledge often hinders students’ ability to communicate effectively. This study aimed to examine the effectiveness of the Duolingo application in enhancing English vocabulary mastery among eighth-grade students at SMPN 3 Sikur. The research employed a quantitative approach using a pre-experimental one-group pretest and post-test design. The participants consisted of 20 students from class VIII B, selected through purposive sampling. Data were collected using a 40-item multiple-choice vocabulary test administered before and after the treatment. The treatment involved regular use of the Duolingo application over a specified instructional period. The instrument demonstrated high reliability, with a KR-20 coefficient of 0.82. Data analysis was conducted using SPSS version 22, including descriptive statistics, normality and homogeneity tests, and a paired samples t-test. The results revealed a substantial increase in students’ mean vocabulary scores, from 42.25 on the pre-test to 73.00 on the post-test. The paired samples t-test indicated a statistically significant difference between pre-test and post-test scores (p < 0.05), confirming the effectiveness of Duolingo in improving students’ vocabulary mastery. These findings suggest that Duolingo, as a mobileassisted language learning tool, can serve as an effective supplementary medium for vocabulary instruction. The study provides pedagogical implications for integrating gamified mobile applications into English language teaching to support learner engagement and vocabulary development.